RBD- specific Th1 responses are associated with vaccine-induced protection against SARS-CoV-2 infection in patients with hematological malignancies - Camille Bigenwald; Yacine Haddad; Cassandra Thelemaque; Agathe Carrier; Roxanne Birebent; Pierre Ly; Caroline Flament; Imran Lahmar; Eric de Sousa; Markus Maeurer; Makoto Miyara; Tarek Assi; et al. (OncoImmunology)
The SARS-CoV-2 pandemic still represents a threat for immunosuppressed and hematological malignancy (HM) bearing patients, causing increased morbidity and mortality. Given the low anti-SARSCoV-2 IgG titers post-vaccination, the COVID-19 threat prompted the prophylactic use of engineered anti-SARS-CoV-2 monoclonal antibodies. In addition, potential clinical significance of T cell responses has been overlooked during the first waves of the pandemic, calling for additional in-depth studies. We reported that the polarity and the repertoire of T cell immune responses govern the susceptibility to SARS-CoV-2 infection in health care workers and solid cancer patients. Here, we longitudinally analyzed humoral and cellular immune responses at each BNT162b2 mRNA vaccine injection in 47 HM patients under therapy. Only one-third of HM, mostly multiple myeloma (MM) bearing patients, could mount S1-RBD-specific IgG responses following BNT162b2 mRNA vaccines. This vaccine elicited a S1-RBD-specific Th1 immune response in about 20% patients, mostly in MM and Hodgkin lymphoma, while exacerbating Th2 responses in the 10% cases that presented this recognition pattern at baseline (mostly rituximab-treated patients). Performing a third booster barely improved the percentage of patients developing an S1-RBD-specific Th1 immunity and failed to seroconvert additional HM patients. Finally, 16 patients were infected with SARS-CoV-2, of whom 6 developed a severe infection. Only S1-RBD-specific Th1 responses were associated with protection against SARS-CoV2 infection, while Th2 responses or anti-S1-RBD IgG titers failed to correlate with protection. These findings herald the paramount relevance of vaccine-induced Th1 immune responses in hematological malignancies.